2013
DOI: 10.1093/gerona/glt198
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Shc Proteins on Life Span in Mice

Abstract: The signaling molecule p66Shc is often described as a longevity protein. This conclusion is based on a single life span study that used a small number of mice. The purpose of the present studies was to measure life span in a sufficient number of mice to determine if longevity is altered in mice with decreased Shc levels (ShcKO). Studies were completed at UC Davis and the European Institute of Oncology (EIO). At UC Davis, male C57BL/6J WT and ShcKO mice were fed 5% or 40% calorie-restricted (CR) diets. In the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
0
27
1
Order By: Relevance
“…Indeed, lung emphysema and fibrosis are frequent in both G3 and later generations of TERC −/− independently by the p66SHC deletion, although we could not establish that lung dysfunction is the cause of death of these mice. Histiocytic sarcoma was reported to be the most frequent tumor lesion in C57Bl/6 mice, including p66SHC −/− (Ramsey et al ., 2014) and TERC −/− (Khoo et al ., 2007) models. In any case, the early mortality of TERC −/− mice is not determined by p66SHC suggesting that oxidative stress and telomere attrition do not cooperate to determine lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lung emphysema and fibrosis are frequent in both G3 and later generations of TERC −/− independently by the p66SHC deletion, although we could not establish that lung dysfunction is the cause of death of these mice. Histiocytic sarcoma was reported to be the most frequent tumor lesion in C57Bl/6 mice, including p66SHC −/− (Ramsey et al ., 2014) and TERC −/− (Khoo et al ., 2007) models. In any case, the early mortality of TERC −/− mice is not determined by p66SHC suggesting that oxidative stress and telomere attrition do not cooperate to determine lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…4), and Shc mice developed by the Pelicci group (ShcP or ShcPelicci, also known as p66Shc(Ϫ/Ϫ, Refs. 3,4,8,9). Names in literature for these two models can be described by these definitions: ShcL, ShcProlla; ShcKO, ShcP ϭ ShcPelicci ϭ p66Shc(Ϫ/Ϫ).…”
mentioning
confidence: 99%
“…This is not the first time a study was unable to replicate the increase in lifespan shown in an original study. For example, knockout mouse models for the signaling molecule p66Shc (p66shc −/− mice) (Migliaccio et al., 1999), insulin receptor substrate 2 (Irs2) (Irs2 +/− mice) (Taguchi, Wartschow & White, 2007), and the IGF1 receptor ( Igf1r +/− mice) (Holzenberger et al., 2003) all showed substantial lifespan extension in initial reports that was not confirmed in follow‐up studies (Bokov et al., 2011; Ladiges et al., 2009; Liang et al., 2003 ; Ramsey et al., 2014; Selman, Lingard, Gems, Partridge & Withers, 2008; Selman et al., 2007; Unnikrishnan, Deepa, Herd & Richardson, 2017). Differences in genetic background can potentially modulate lifespan results.…”
Section: Discussionmentioning
confidence: 99%